2020
DOI: 10.1101/2020.07.07.20143024
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Digestive Manifestations in Patients Hospitalized with COVID-19

Abstract: Background: The prevalence and significance of digestive manifestations in COVID-19 remain uncertain. Methods: Consecutive patients hospitalized with COVID-19 were identified across a geographically diverse alliance of medical centers in North America. Data pertaining to baseline characteristics, symptomatology, laboratory assessment, imaging, and endoscopic findings from the time of symptom onset until discharge or death were manually abstracted from electronic health records to characterize the pre… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(39 citation statements)
references
References 23 publications
1
36
0
2
Order By: Relevance
“…Using this approach, we find that GTEx lung eQTLs lie closer to predicted causal mutations amongst the 42 putative selected loci than for any other tissue (P=3.10 −5 ; Figure 5). Several additional tissues known to be negatively affected by coronavirus – blood and arteries (Bao et al, 2020; Grosse et al, 2020), adipose tissue (Michalakis and Ilias, 2020) and the digestive tract (Elmunzer et al, 2020) – also exhibit closer proximities between putative causal loci and tissue-specific eQTLs than expected by chance (Figure 5). Interestingly, the spleen shows no tendency for eQTLs to lie closer to selected loci than expected around 900 generations ago compared to other evolutionary times, perhaps because the spleen is replete with multiple types of immune cells that might be more prone to more regular adaptation in response to diverse pathogens over time, and less prone to adaptive bursts restricted over time in response to a specific pathogen (Quintana-Murci, 2019).…”
Section: Resultsmentioning
confidence: 95%
“…Using this approach, we find that GTEx lung eQTLs lie closer to predicted causal mutations amongst the 42 putative selected loci than for any other tissue (P=3.10 −5 ; Figure 5). Several additional tissues known to be negatively affected by coronavirus – blood and arteries (Bao et al, 2020; Grosse et al, 2020), adipose tissue (Michalakis and Ilias, 2020) and the digestive tract (Elmunzer et al, 2020) – also exhibit closer proximities between putative causal loci and tissue-specific eQTLs than expected by chance (Figure 5). Interestingly, the spleen shows no tendency for eQTLs to lie closer to selected loci than expected around 900 generations ago compared to other evolutionary times, perhaps because the spleen is replete with multiple types of immune cells that might be more prone to more regular adaptation in response to diverse pathogens over time, and less prone to adaptive bursts restricted over time in response to a specific pathogen (Quintana-Murci, 2019).…”
Section: Resultsmentioning
confidence: 95%
“…To date, the published studies have only reported on the presence or not of nausea and vomiting, with no descriptions of their severity, comparable with those used routinely to assess these symptoms as side‐effects of anticancer chemotherapy 61 . A study of almost 2000 patients reported that GI symptoms (predominantly diarrhea, nausea, vomiting, and abdominal pain) were “judged to be mild” in 74% of patients, 31 which could imply it was more severe in the remaining 26%. Additionally, there is a paucity of data on the temporal pattern of nausea and vomiting during the course of the disease.…”
Section: How Good Is the Epidemiological Data On The Incidence Of Naumentioning
confidence: 99%
“…The incidence of nausea and/or vomiting and diarrhea from 41 clinical studies 1,2,4,5,16,22–57 : nausea, n = 34; vomiting, n = 39; diarrhea, n = 39. Values for individual studies are shown together with the median and 95% confidence intervals.…”
Section: How Good Is the Epidemiological Data On The Incidence Of Naumentioning
confidence: 99%
“…It is likely that well-established risk factors, such as age and medical comorbidities (including cirrhosis), are more important predictors of COVID-19 outcomes than are liver biochemistries. Moreover, in a recent large cohort study of hospitalized patients with COVID-19, the prevalence of severe acute liver injury was exceedingly low [ 10 ]. Third, the potential risks of liver biopsy for COVID-19 will extend to both patient and staff.…”
mentioning
confidence: 99%